MODELLING THE SUCCESSFUL INTEGRATION OF MOBILE AUGMENTED REALITY TECHNOLOGY (MART) AMONG MALAYSIAN PRE-SERVICE TEACHERS - Mohd Khairezan Rahmat; Nur Nabihah Mohamad Nizar, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The integration of mobile augmented reality technology (MART) into the education system since the last two decades have brought to the topic of discussion among many scholars. Although numerous studies have highlighted its huge potentials and benefits toward both teacher's and students' teaching and learning process, several researchers reported that teachers’ readiness to integrate mobile augmented reality technology is still uncertain. Given the importance and consideration of research that has been undertaken, the present study was set to examine the Malaysian pre-service teachers’ readiness toward integrating MART into their learning and future teaching process. The Technology Acceptance Model (TAM) was adapted as the theoretical grounding of the study in explaining and predicting pre-service teachers’ decision to integrate mobile augmented reality technology. Data of the study was gathered from 303 Malaysian pre-service teachers and were analysed using the descriptive analysis of SPSS and Partial Least Square (PLS) of Structural Equation Modelling (SEM). Findings from the study demonstrate that pre-service teachers’ readiness to integrate MART is at a moderate level. The study also suggested that pre-service teachers’ perceived usefulness has the most significant direct effect on their decision to integrate MART. On the basis of these findings a purpose model is developed, and implications of theory development, practices, and policymaking are discussed in this paper.